The expression of sexuality in people with psychosis - breaking the taboos - McCann, Edward (My University, 2000)
While mental health professionals should recognize that people suffering from schizophrenia have sexual and relationship requirements, there appears to be a failure to address adequately the subject of human sexuality, particularly in the area of psychosocial rehabilitation. The broad aim of this small study was to identify the sexual and relationship needs of people being cared for in hospital and preparing for a return to community living. The objectives of the study were to discover the clients' sexual expressions in the past and present, and to try to elicit hopes and aspirations for the future. An attempt was made to uncover some of the obstacles to the expression of sexuality and explore some of the clients' subjective experiences of the issues. The number of respondents was 11 from a possible 15. Data were collected through: a questionnaire on demographic characteristics; an adapted version of a questionnaire investigating the determinant factors of sexual behaviour through life; and a semi-structured interview devised to elicit subjective experiences regarding sexual expression. The findings show that people with psychotic illness are prepared to discuss issues relating to sex and relationship matters. No interviews had to be prematurely terminated. No exacerbations of symptoms were noted. All of the respondents showed an openness to discuss a range of intimate feelings. Most respondents seemed hopeful about the opportunity to form intimate and fulfilling relationships in the future. A drive towards more rigorous holistic nursing assessments and appropriate psychosocial responses is proposed.
PUBLISHED
Keywords: schizophrenia; Psychosis; Service users; Sexuality